Analytical aspects of selenium(+4)-rhodium(+3) interactions under voltammetric conditions - Zelić, Marina, kemičarka (Array, 2008)
Abstract: Voltammetry of selenium(+4)-rhodium(+3) system was studied in different electrolyte solutions with special attention paid to possible application of the observed effects in selenite determination at trace levels. Although the signals obtained from such mixtures can be more than 200 times higher than those resulting from simple selenium(+4) solutions without rhodium(+3) added, it remains questionable how such results could be applied in practice. The main problem is data treatment because (generally) current – concentration plot is not a straight line with zero intercept. Additionally, its shape changes with the selenite concentration range. The problem is illustrated taking as an example selenium(+4) determination in solutions of selenium(+6). At present, results obtained in the system of interest seem to be important as phenomena and possible indicators of some catalytic processes. Before their application in trace analysis the answers to some general questions should be found